1990
DOI: 10.1136/gut.31.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gastrin cell number, serum, antral mucosa and luminal gastrin concentration and gastric acidity in antral atrophic gastritis.

Abstract: The aim of our study was to investigate the relationship between gastrin producing cell density with antral mucosa, luminal and serum gastrin concentration in antral atrophic gastritis. Our study group consisted of 17 patients: six with mild atrophic gastritis, seven with moderate atrophic gastritis and four with severe atrophic gastritis. None of the patients had type-A atrophic gastritis but the body mucosa was affected by superficial gastritis at various extent in some. A group of 15 healthy subjects served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
5
12
0
2
Order By: Relevance
“…The missing negative correlation between antral atrophy and gastrin‐17 levels are furthermore in line with previous reports, other than those on evaluation of the GastroPanel 27,28 . Two potential explanations could be former PPI treatment and H. pylori infection; both are known to induce gastrin secretion.…”
Section: Discussionsupporting
confidence: 90%
“…The missing negative correlation between antral atrophy and gastrin‐17 levels are furthermore in line with previous reports, other than those on evaluation of the GastroPanel 27,28 . Two potential explanations could be former PPI treatment and H. pylori infection; both are known to induce gastrin secretion.…”
Section: Discussionsupporting
confidence: 90%
“…Gastrin can stimulates β-cell neogenesis and replication, and reduces β-cell apoptosis, resulting in expansion of β-cell mass and improved glucose homeostasis3031. With the progression of the severity of gastric atrophy, there is a progressive reduction in gastric acidity and a progressive increase in luminal gastrin concentrations32. In this study, there was a significant inverse correlation between serum PG I/II ratio and HOMA2%B.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, we observed neither a change in the gastrin level nor in GERD occurrence between H. pylori-infected and non-infected state. In contrast to these hypotheses, we could not demonstrate any relationship between gastrin and GERD, which was comparable with a few studies in the literature (18)(19)(20)(21)(22)(23)(24). One of the reasons for this difference can be the predominant corpoantral infection in our patients.…”
Section: Discussionsupporting
confidence: 79%